Hypochlorite-modified albumin colocalizes with RAGE in the artery wall and promotes MCP-1 expression via the RAGE-Erk1/2 MAP-kinase pathway - Marsche, Gunther (FASEB J, 2007)
Signal transduction via the endothelial receptor for advanced glycation end products (RAGE) plays a key role in vascular inflammation. Recent observations have shown that the myeloperoxidase-H(2)O(2)-chloride system of activated phagocytes is highly up-regulated under inflammatory conditions where hypochlorous acid (HOCl) is formed as the major oxidant. Albumin, an in vivo carrier for myeloperoxidase is highly vulnerable to oxidation and a major representative of circulating advanced oxidized proteins during inflammatory diseases. Immunohistochemical studies performed in the present study revealed marked colocalization of HOCl-modified epitopes with RAGE and albumin in sections of human atheroma, mainly at the endothelial lining. We show that albumin modified with physiologically relevant concentrations of HOCl, added as reagent or generated by the myeloperoxidase-H(2)O(2)-chloride system, is a high affinity ligand for RAGE. Albumin, modified by HOCl in the absence of free amino acids/carbohydrates/lipids to exclude formation of AGE-like structures, induced a rapid, RAGE-dependent activation of extracellular signal-regulated kinase 1/2 and up-regulation of the proinflammatory mediator monocyte chemoattractant protein-1. Cellular activation could be blocked either by a specific polyclonal anti-RAGE IgG and/or a specific mitogen-activated protein-kinase kinase inhibitor. The present study demonstrates that HOCl-modified albumin acts as a ligand for RAGE and promotes RAGE-mediated inflammatory complications.